Novel Steroidal Glycosides from the Bulbs of Lilium pumilum - Yukiko Matsuo (Molecules, 2015)
Examination of the bulbs of Lilium pumilum (Liliaceae) led to the isolation of four novel steroidal glycosides (1–4) with a 2,3,4-trisubstituted β-d-glucopyranosyl unit. In 1 and 3, the α-L-arabinopyranosyl moiety is linked to C-3 of the inner trisubstituted β-D-glucopyranosyl group and is present as an usual 4C1 conformation. In contrast, in 2 and 4, the α-L-arabinopyranosyl moiety, which is attached to C-4 of the inner trisubstituted β-D-glucopyranosyl group, is present as a 1C4 conformation. The structures of the new steroidal glycosides were determined based on the results of spectroscopic analyses, including two-dimensional (2D) NMR data and hydrolysis.